Regional Synergy Model in Strengthening Islamic Social Finance: Southeast Asian Perspective - Zakiyah, Hanifah; Andrini, Rozi (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2025)
Islamic Social Finance (ISF) is a vital instrument in promoting economic justice in Islam through the management of zakat, infaq, sadaqah, and waqf (ZISWAF). In Southeast Asia, Muslim-majority countries such as Indonesia, Malaysia, and Brunei have developed national-level ISF systems. However, regulatory fragmentation, the absence of cross-border coordination, and suboptimal technological integration remain significant barriers to collective efforts aimed at empowering the Muslim community at the regional level. This research designs an adaptive and sustainable regional synergy model in strengthening Islamic Social Finance in Southeast Asia. The research employs a descriptive qualitative approach, relying on in-depth literature analysis of regulations, institutional reports, and academic publications in the field of Islamic social finance. Data were analyzed using content analysis to identify challenges and opportunities for inter-country collaboration and to develop a conceptual framework for cross-border synergy. The findings reveal a high potential for ISF in the region, supported by a large Muslim population, active managing institutions, and advancing digitalization in several countries. Nonetheless, disparities in legal systems, lack of data sharing, and the dominance of national approaches serve as major constraints. This article proposes the establishment of a synergy model consisting of a regional coordinating institution, a Southeast Asia ISF data center, and a shared digital platform for managing cross-border ZISWAF funds. The study recommends ASEAN support in creating a regional legal framework for ISF, the development of cross-national human resources, and collaborative research to ensure effective and sustainable implementation.